Designing Data-Driven Business Models: AI Integration and Industrial Data Fusion Across Hierarchical Levels (International Journal of Computer Science and Engineering, 2026)
With the increasing integration of Artificial Intelligence in manufacturingprocesses and the advent of Industry 4.0, businesses are undergoing a transformationfrom traditional product-centric models to data-driven, service-oriented models. Thispaper systematically analyzes the performance of five hierarchical levels across fivedimensions: data, processes, IT systems, interfaces, and standards, through a literaturereview and industrial case analysis. It evaluates the current state and futuredevelopments of each level and explores how intelligent sensor systems can drive thedevelopment of new business models in manufacturing